Molecular characterization of human Echinococcus isolates and the first report of E. canadensis (G6/G7) and E. multilocularis from the Punjab Province of Pakistan using sequence analysis - Khan, Aisha; Ahmed, Haroon; Simsek, Sami; Liu, Hua; Yin, Jianhai; Wang, Ying; Cao, Jianping (Bmc, 2020)
Background Echinococcosis is a zoonotic parasitic disease causing serious health problems in both humans and animals in different endemic regions across the world. There are two different forms of human echinococcosis: Cystic Echinococcosis (CE) and Alveolar Echinococcosis (AE). CE is caused by the larval stage of Echinococcus granulosus sensu lato and AE by the larval stage of Echinococcus multilocularis. Geographically, CE is universally distributed, while AE is prevalent in the northern hemisphere. Although the disease is endemic in neighboring countries (China, Iran and India) of Pakistan, there are limited reports from that country. Besides, there are no comprehensive data on the genotyping of Echinococcus species in humans based on sequence analysis. This study aimed to detect the presence of human CE and to identify Echinococcus spp. in human isolates through genetic characterization of hydatid cysts in the Punjab Province of Pakistan. Methods Genetic analysis was performed on 38 human hydatid cyst samples collected from patients with echinococcosis using mitochondrial cytochrome c oxidase subunit 1 (cox1), cytochrome b (cytb) and NADH subunit 1 (nad1). Patient data including age, epidemiological history, sex, and location were obtained from hospital records. Results According to the sequence analysis we detected E. granulosus sensu stricto (n = 35), E. canadensis (G6/G7) (n = 2), and E. multilocularis (n = 1). Thus, the majority of the patients (92.1%, 35/38) were infected with E. granulosus s.s. This is the first molecular confirmation of E. canadensis (G6/G7) and E. multilocularis in human subjects from Pakistan. Conclusions These findings suggested that E. granulosus s.s. is the dominant species in humans in Pakistan. In addition, E. canadensis (G6/G7) and E. multilocularis are circulating in the country. Further studies are required to explore the genetic diversity in both humans and livestock.
Keywords: E; granulosus sensu stricto; E; canadensis; E; multilocularis; Human; Genotyping; Pakistan